Investigation about the consumption of edible flowers in Portugal - Guiné, Raquel (2019)
Nowadays the interest in the use of edible flowers for gastronomy purposes has increased. Therefore, the aim of this study was to evaluate the extent to which socio demographic characteristics influenced the knowledge and consuming habits related to edible flowers in a sample of 247 Portuguese adults. The results revealed that this subject is not unknown for the majority of the participants and that they were aware of some of aspects related to the consumption of this kind of product. In general, edible flowers are consumed sporadically, cooked or incorporated in salads and mainly because of their taste. It was also observed that gender as well as the area of work or studies influenced the participants’ knowledge and some of the consuming habits related to edible flowers. However, there were still some aspects about which the participants revealed some confusion, such as for the example the risks related to their consumption. Hence, it is important to continue with studies in this area, in order to clarify and deepen the knowledge about the use of edible flowers in gastronomy.